THE ROLE OF KINESTHETIC INTELLIGENCEIN PROFESSIONAL EDUCATION - Umirzoqova Surayyo Xudoyberdiyevna (Western European Studies, 2025)
This article explores the significance of kinesthetic intelligence within the context of professional education. It outlines the conceptual framework of bodily-kinesthetic intelligence, its relevance to various fields such as medicine, engineering, pedagogy, and the arts, and emphasizes its role in developing practical competencies. The paper also discusses how kinesthetic learning approaches enhance students' engagement, knowledge retention, and skill application in real-world settings. Through a synthesis of theoretical analysis and empirical data, this study highlights the importance of integrating kinesthetic strategies into professional education to support holistic student development
Keywords: kinesthetic intelligence; professional education; bodily-kinesthetic learning